From the national system of electronic libraries to the National Electronic Library of Ukraine: evolution of views - Zbanatska Oksana (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The purpose of the article is to investigate the evolution of views from the national system of electronic libraries to the creation of the National Electronic Library of Ukraine. The research methodology is based on the application of general scientific and special methods of cognition, in particular the systemic, historical and terminological approach, analysis, synthesis, generalization. The scientific novelty of the article lies in the generalization of information and expansion of ideas about the views of scientists regarding the creation of the National Electronic Library of Ukraine. Conclusions. The first developments in the organization of the national system of electronic libraries in the form of a sketch project were presented in 1996, the formation and functioning of both the system of electronic libraries and individual electronic libraries. In particular, this is a matter of terminology, definition of structure and functions, classification, legal framework, copyright on the Internet, history of creation and prospects of electronic libraries, etc. In 2016, the question of the creation of the National Electronic Library and corporatism arose again, but the next attempt was of a declarative nature. 2023 announced the start of a new project to create the National Electronic Library of Ukraine with the support of UNESCO and IFLA, which is planned to be implemented in four stages during 2024-2029. This is a complex task that requires the solution of substantive, methodological, organizational, technological, technical and financial challenges. Only their comprehensive solution will allow to create a modern National Electronic Library of Ukraine. Only their comprehensive solution will allow to create a modern National Electronic Library of Ukraine.